Mitochondrial DNA-based reassessment of Antennablennius Fowler (Blenniidae: Salariini) from the north-western Indian Ocean, with resurrection of A. persicus (Regan) - Estekani, Sanaz; Bogorodsky, Sergey V.; Zajonz, Uwe; Hundt, Peter J.; Siahsarvie, Roohollah; Aliabadian, Mansour (Zootaxa, 2024)
Seven Operational Taxonomic Units within the blenniid genus Antennablennius are recognised from the north-western Indian Ocean, based on the Cytochrome oxidase-c subunit I gene (CO1). Five of them can be referred to nominal species with certainty. Two additional distinct lineages originate from the Persian Gulf and the Gulf of Oman, and the Socotra Archipelago. They were initially, morphologically, identified as A. adenensis Fraser-Brunner, 1951, yet could hitherto not be referred to this species with certainty, requiring further genetic data. Detailed descriptions accompanied by photographs are provided for six species, including A. adenensis. Antennablennius persicus (Regan, 1905) is resurrected from the synonymy of A. bifilum (Günther, 1861) and re-described based on specimens from the Iranian coast of the Persian Gulf and Gulf of Oman, increasing the number of valid species in the genus to eight. The former differs from the latter species in details of morphology and coloration, supported by genetic data. A revised key to all species of the genus is included. A phylogenetic investigation of the genus based on Maximum Likelihood (ML) and Bayesian Inference (BI) analyses of the CO1 data is presented for the first time.